Hydrothermal synthesis of pristine nickel diselenide (NiSe2) and Co induced nickel diselenide (NiCoSe2) nanoparticles with enhanced electrochemical behaviour for supercapacitor applications - S. Saranya; S. Suthakaran; S. Dhanapandian; A. Dinesh; Rajendra P. Patil; Manikandan Ayyar; Lalitha Gnanasekaran; S. Santhoshkumar (Results in Chemistry)
In this work, pristine nickel diselenide (NiSe2) and Co induced nickel diselenide (NiCoSe2) nanoparticles (NPs) were prepared through a facile hydrothermal method. The prepared NPs were examined using the XRD, FT-IR, SEM/EDX, TEM/SAED, XPS, VSM and cyclic voltammetry (CV) analysis. XRD patterns confirmed the cubic crystal structure of the prepared samples. In FTIR, a minor stretching vibration were observed in pure NiSe2 and NiCoSe2 samples. SEM images exhibited spherical ball like clusters, agreed well with TEM results. XPS results confirmed the chemical compositions and binding energy of pure and NiCoSe2 NPs. Room temperature hysteresis measurement revealed that the sample is belonging to ferromagnetic nature and the increased saturation magnetization value is due to the synergetic effect of Ni and Co. The magnetic studies of the present work suggesting that these samples have potential for data storage applications. The specific capacitance value for the pure is found to be 384 F g−1 and increased to 860 F g−1 for NiCoSe2 at the scan rate of 2 mVs−1, showed that the synergetic effect of bimetals has improved the electrochemical performance of NiSe2 nanoparticles.